A decolonial reading of the herald’s construction of the local/ foreign coach debate - Makoma, James (Midlands State University, 2019)
Zimbabwe, like any other post colonial state in Africa is grappling with coloniality and is trying to decolonize. A lot of researches have embarked in decolonial reading of other phenomena, but no research has examined coloniality in the framing of the local and foreign coach in Zimbabwe’s biggest newspaper, The Herald. The research is theoretically grounded in decolonial theories and also makes use of framing theory. The study employs qualitative research approach, case study design and deploys archival research and interview in gathering data. The study shows the prevalence of coloniality at work in sport, in Zimbabwe playing out The Herald, which, is the main newspaper and the biggest in terms of circulation. Journalist and football administrators are both found culpable in perpetuating coloniality.